The taxonomic diversity of the Ju|'hoansi hunter-gatherer intestinal microbiome in Tsumkwe, Namibia - Rifkin, Riaan (University of Pretoria, 2022)
Dissertation (MSc (Bioinformatics))--University of Pretoria, 2021.